2011
DOI: 10.1128/jvi.02120-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Dendritic Cells Infected with the Nonpathogenic Mopeia Virus Induce Stronger T-Cell Responses than Those Infected with Lassa Virus

Abstract: The events leading to death in severe cases of Lassa fever (LF) are unknown. Fatality seems to be linked to high viremia and immunosuppression, and cellular immunity, rather than neutralizing antibodies, appears to be essential for survival. We previously compared Lassa virus (LV) with its genetically close but nonpathogenic homolog Mopeia virus (MV), which was used to model nonfatal LF. We showed that strong and early activation of antigen-presenting cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 77 publications
4
70
0
Order By: Relevance
“…Upon infection, DC remain unactivated, and M produce only very small amounts of type I IFN (13). Low and late T cell responses without cytotoxicity or memory occur during LASV infection of DC in an in vitro model (14). Similarly, we have shown that LASV-infected DC do not induce NK cell activation in vitro (15).…”
mentioning
confidence: 75%
“…Upon infection, DC remain unactivated, and M produce only very small amounts of type I IFN (13). Low and late T cell responses without cytotoxicity or memory occur during LASV infection of DC in an in vitro model (14). Similarly, we have shown that LASV-infected DC do not induce NK cell activation in vitro (15).…”
mentioning
confidence: 75%
“…Recovery and protection are dependent on T cell responses and are not associated with the production of specific IgG. In human DC-T cell cocultures, LASV induced only weak memory phenotype markers, while MOPV strongly stimulated CD8 ϩ and CD4 ϩ T cells, activation markers, proliferative responses, and CTL activities (49). We speculate that the TLR2-mediated stimulation of cytokines in MOPV-infected cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The production of proinflammatory cytokines results in the activation of antigenpresenting cells and T cell stimulation in the adaptive immune response. Indeed, recent results showed that MOPV infection of human dendritic cells (DCs) induced strong T cell responses and memory cells, while LASV infection did not (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(C) Total cellular RNA was extracted using TRIzol reagent (Invitrogen). The levels of IFN-␤ (left graphs), IFN-␣1 (middle graphs), and IFN-␣2 (right graphs) mRNAs in DC (upper graphs) and MP (lower graphs) mock infected or infected with the different recombinant or WT LASV or MOPV were determined by quantitative RT-PCR 18 to 48 h after infection (MOI ϭ 2) as previously described (39). The results reported are the numbers of copies of the mRNA considered/number of copies of ␤-actin mRNA and represent the mean Ϯ standard error from three independent experiments (different donors).…”
mentioning
confidence: 99%